Strategy to Maintain the Cinema Industry in the Middle of Development of Internet Technology - Dipa Mulia, Muchsin Saggaff Shihab (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
Internet technology has been utilized in many sectors of business including in the film industry. People are using internet technology to replace the newspaper and television and also creating a new platform (computer, cellular phone and other types of gadget) to watch a film, it threats the cinema industry.Â This research aims to formulate the strategy of cinema industry to survive in the middle of internet technology. The motive of cinema-goers to watch the film becomes the main issue in this research. The influence of information, personnel film, word of mouth and cinema-quality to cinema-goers are evaluated. Hundred and twenty-eight cinema-goers involved as respondents. Structure Equation Modelling (SEM) is used to analyze the data. The research revealed that the cinema-goers had a specific expectation of the cinema industry that cannot be replaced by internet technology.